20.6k views
5 votes
Could you please Help Me?

The work of a student to solve the equation
2(5y − 2) = 12 + 6y is shown below:

Step 1: 2(5y − 2) = 12 + 6y
Step 2: 7y − 4 = 12 + 6y
Step 3: y − 4 = 10
Step 4: y = 14
Step 5: y = 7
In which step did the student first make an error and what is the correct step? Step 2: 7y − 4 = 6 + 3y
Step 2: 10y − 4 = 12 + 6y
Step 3: 5y − 2 = 2(10 + 3y)
Step 3: 2(5y − 2) = 10 + 3y

2 Answers

1 vote
STEP 4 : 10 Y - 4 = 10 + 3Y
step 5 : 7y = 14
step 6 = 14 / 7 = 2
y = 2
User Luke Needham
by
6.2k points
5 votes
In step two it should be 10y-4=12+6y
User Yatish Mehta
by
5.6k points